A Short Access to Symmetrically α,α-Disubstituted α-Amino Acids from Acyl Cyanohydrins - Boukattaya, Fatma; Caillé, Julien; Ammar, Houcine; Rouzier, Florian; Boeda, Fabien; Pearson-Long, Morwenna S. M.; Bertus, Philippe (Synthesis, 2016)
A straightforward synthesis of symmetrically α,α-disubstituted α-amino acids is presented. The key step of this process relies on the efficient double addition of Grignard reagents to acyl cyanohydrins to provide N-acyl amino alcohols selectively in good yields. The chemoselectivity of the reaction was modulated by the nature of the acyl moiety. Eleven amino acids were prepared, including the particularly simple divinylglycine, which is not easily accessible by using conventional methods.
Keywords: amino acids; cyanohydrins; Grignard reagents; nitriles; solvent effects